Successful use of olanzapine in adolescent monozygotic twins with catatonic schizophrenia resistant to electroconvulsive therapy: case report - Dudova, Iva; Hrdlicka, Michal (Neuro endocrinology letters, 2008)
We describe a case of monozygotic (MZ) male twins (14.6 years old) who suffered from a severe form of catatonic schizophrenia. On admission, the principal symptoms of the brothers were stupor, mutism, catatonic posturing, rigidity, negativism, and refusal of food and liquids. They were treated with electroconvulsive therapy (ECT) with no effect (twin A) and almost no effect (twin B). Both twins improved with initiation of olanzapine therapy. Twin B showed a marked improvement by week 2 on a dose of 10 mg daily (qd). Improvement in twin A was seen by week 4 on a dose of 15 mg qd. Twin B was discharged after 8 weeks and twin A after 11 weeks of olanzapine treatment. This appears to be the first report on concordant positive responses to olanzapine in MZ twins with catatonic schizophrenia, as well as, the first report on concordant resistance to ECT.
Keywords: olanzapin; elektrokonvulzívní terapie; antipsychotika; Antipsychotic Agents; Twins, Monozygotic; výsledek terapie; dvojčata monozygotní; Adolescent; Electroconvulsive Therapy; lidé; Olanzapine; Schizophrenia, Catatonic; Treatment Outcome; Male; schizofrenie katatonická; Benzodiazepines; benzodiazepiny; mužské pohlaví; mladiství; Humans